A new approach to hypergeometric transformation formulas - Otsubo, Noriyuki (The Ramanujan journal, 2021)
We give a new method to prove in a uniform and easy way various transformation formulas for Gauss hypergeometric functions. The key is Jacobi’s canonical form of the hypergeometric differential equation. Analogy for q -hypergeometric functions is also studied.